Quality analysis and antioxidant activity of different types of tea powder - Yutong Ye; Zeyi Ai; Ronglin Li; Yang Tian; Yiyang Yang (Food Production, Processing and Nutrition, 2024)
Abstract As a natural product with health benefits, tea powder (TP) is widely used in food processing field. In order to explore sensory evaluation, quality components and antioxidant activities among different types of TP, matcha TP, Huangjinya green TP, oolong TP, black TP and Pu-erh TP were used as the research objects. Our results showed that total scores of sensory evaluation of unfermented TPs were higher than those of fermented TPs, whilst the colour of those unfermented TPs was more bright. Furthermore, taste attributes showed that sweetness was conducive to the formation of the taste of black TP, and aftertaste-bitterness was beneficial to matcha and Pu-erh TP. Umami was suggested as a vital contributing factor to the mellow taste of Huangjinya green TP, while sourness and bitterness were not propitious to form the taste quality of tea powder. The non-volatile quality components analysis revealed that tea powders with more fermentation usually contained fewer amino acids and catechins, but glutamate and gamma-aminobutyric acid were higher in black TP than in oolong TP. Theanine, glutamic acid and arginine were the main iconic components affecting the amino acid composition of different types of tea powder in our study. Meanwhile, the contents of ester catechins (ECG, EGC, EGCG) in black TP and Pu-erh TP were significantly lower than those in green TP and oolong TP. In addition, the free radical scavenging ability of unfermented TPs were stronger than that of fermented TPs. Therefore, to maximize the health benefits and sensory attributes of different types of TP, the use of unfermented tea powder is recommended. However, different manufacturing process of tea powder can enrich the taste of tea foods, thus giving people more choices. Graphical Abstract